2013
DOI: 10.3389/fpsyt.2013.00139
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Glia Interaction as a Possible Glue to Translate the Mind-Brain Gap: A Novel Multi-Dimensional Approach Toward Psychology and Psychiatry (R1)

Abstract: Neurons and synapses have long been the dominant focus of neuroscience, thus the pathophysiology of psychiatric disorders has come to be understood within the neuronal doctrine. However, the majority of cells in the brain are not neurons but glial cells including astrocytes, oligodendrocytes, and microglia. Traditionally, neuroscientists regarded glial functions as simply providing physical support and maintenance for neurons. Thus, in this limited role glia had been long ignored. Recently, glial functions hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 96 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…On the basis of such pilot investigations, we have hypothesized that inflammation and oxidative stress may be linked to the underlying pathophysiology of hikikomori , similarly to other psychiatric disorders . Microglia play crucial roles in brain inflammation via releasing free radicals and inflammatory cytokines, such as interleukin‐6 and tumor necrosis factor‐α, and activation of microglia has recently been proposed to exist in various psychiatric disorders, including schizophrenia, depression, bipolar disorder, and autism . In addition, microglial overactivation is proposed to exist in the brains of suicide victims and suicidal individuals, especially via the tryptophan–kynurenine pathway .…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of such pilot investigations, we have hypothesized that inflammation and oxidative stress may be linked to the underlying pathophysiology of hikikomori , similarly to other psychiatric disorders . Microglia play crucial roles in brain inflammation via releasing free radicals and inflammatory cytokines, such as interleukin‐6 and tumor necrosis factor‐α, and activation of microglia has recently been proposed to exist in various psychiatric disorders, including schizophrenia, depression, bipolar disorder, and autism . In addition, microglial overactivation is proposed to exist in the brains of suicide victims and suicidal individuals, especially via the tryptophan–kynurenine pathway .…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
“…76,[83][84][85][86][87] Microglia play crucial roles in brain inflammation via releasing free radicals and inflammatory cytokines, such as interleukin-6 and tumor necrosis factor-α, 88,89 and activation of microglia has recently been proposed to exist in various psychiatric disorders, including schizophrenia, depression, bipolar disorder, and autism. 76,86,[90][91][92][93][94][95][96][97] In addition, microglial overactivation is proposed to exist in the brains of suicide victims and suicidal individuals, especially via the tryptophan-kynurenine pathway. [98][99][100][101][102][103] As noted above, a recent epidemiological data analysis showed that hikikomori sufferers are more likely to have suicide risk, 29 thus similar biological mechanisms via microglial activation may exist in hikikomori.…”
Section: Biological Understandings Of Hikikomorimentioning
confidence: 99%
“…Despite the gradual clarification of the biological aspects of depression, [34][35][36][37][38][39][40] the biological basis of depression-related personality traits has not been well clarified. Tryptophan metabolites, especially serotonin, have gathered greater attention in the endeavor to understand the pathophysiology of depression.…”
Section: Fourth Step: Pilot Analysis Of Biological Validitymentioning
confidence: 99%
“…Human major histocompatibility complex (MHC) is a 4‐million‐base pair (Mb) region located on chromosome 6p21, which contains ∼250 genes and encodes classical HLA genes and other immune genes. MHC class I is found on activated microglia and is involved in complement‐mediated synaptic pruning by microglia . MHC molecules were first investigated because of their ability to identify compatibility for allogeneic tissue grafting.…”
Section: Microgliamentioning
confidence: 99%
“…MHC class I is found on activated microglia and is involved in complement-mediated synaptic pruning by microglia. 135,136 MHC molecules were first investigated because of their ability to identify compatibility for allogeneic tissue grafting. They play a wider role in immunological reactions and neurodevelopment.…”
Section: Major Histocompatibility Complexmentioning
confidence: 99%